The Influence of Content Quality and Personalization on Continuous Intention to Subscribe Netflix through the Mediation Of Perceived Value - Haqqo, Cantika Insanil; Isharina, Ikhtiara Kaideni (Profesional Muda Cendekia Publishing, 2024)
Research Aim: This research aims to determine the influence of content quality and personalization on continuous intention to subscribe to Netflix through the mediation of perceived value by following stimulus-organism-response (S-O-R) theory. Design/methodology/approach: This study adopts an explanatory research design employing a quantitative methodology. Non-probability sampling with a purposive sampling technique was utilized, involving a total of 170 respondents consist of Indonesian Netflix users aged 18 or older, who have a monthly subscription and have been subscribing for at least 3 months. The collected data were processed using Partial Least Square Structural Equation Modelling (PLS-SEM) method with SmartPLS4. Hypothesis testing used a bootstrapping system to obtain p-values. Research Findings: The research results show that in the context of Indonesian OTT consumers (1) the content quality and perceived value variables have a positive and significant direct influence on continuous intention to subscribe, and (2) the perceived value variable fully mediates the influence of personalization on the continuous intention to subscribe. Theoretical Contribution/Originality: These results align with the theoretical concept of SOR, which posits that the stimuli in technological environments affect customers' internal states and, in turn, influence their behavioral responses. Keywords: Content quality; personalization; perceived value; continuous intention to subscribe.